Pengaruh Diskon, Tagline Gratis Ongkos Kirim, Dan Shopping Lifestyle Terhadap Keputusan Pembelian Impulsif Pada E-Commerce Shopee (Pada Mahasiswa Universitas Pelita Bangsa Angkatan 2020 Yang Menggunakan E-Commerce Shopee) - Adelia Anggraeni Laksmawan; Langgeng Sri Handayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The increasing interest in shopping online among the public, including students, has resulted in many E-Commerce emerging in Indonesia, one of which is Shopee. Shopee promotional programs such as discounts, free shipping taglines, have made the online shopping platform popular in Indonesia, especially for people who have a shopping lifestyle and tend to make impulse purchases. This research aims to find out the influence of discounts, free shipping taglines, and shopping lifestyle on impulse buying decisions on E-Commerce Shopee, among Pelita Bangsa University students class of 2020. This research uses quantitative methodology, the population is unknown with a sample of 100 students. Data collection used questionnaires that had been distributed, and used the SPSS 27.0 program as a data analysis tool. The results of this research show that discounts have a positive but not significant effect on impulse buying decisions, the free shipping tagline has no effect on impulse buying decisions, and lifestyle shopping has a positive and significant effect on impulsive buying decisions. The discount variable, free shipping tagline, and shopping lifestyle influence impulsive purchasing decisions by 36.1%, and the remainder is influenced by other variables not examined in this penelitian.